Experimental Analysis of Spherical Compression of Warp-Knitted Mesh Spacer Fabrics (Journal of Fiber Bioengineering and Informatics, 2014)
Warp-knitted mesh spacer fabrics are widely used as seat mattress for their excellent pressure-reliefperformance and heat and moisture comfortability; however, action and reaction between human bodyand spacer fabrics are still not well-known, which is attributed to the unknown contacting geometry.The main content dealt with in the paper is to measure surface geometry of warp-knitted mesh spacerfabric under spherical compression, and also to discuss the influence of sphere with different diameters oncompression behaviour. Resin curing method was utilized to fix the surface geometry of compressed warp-knitted mesh spacer fabric, so as to obtain surface geometry functions of spacer fabrics. Experimentalresults demonstrate that the cross-sectional curves of both the non-contacting part and contactingpart are exponential function and circular function, respectively. Moreover, correlations of maximumcompressional strain between spherical compressions from different spheres were calculated, which revealsthat there exist a good correlation between maximum compressional strain decrease and increasingdiameter of sphere. The paper is helpful for studying compression behavior of warp-knitted mesh spacerfabrics and its interaction with different parts of the body in mattress materials.
Keywords: Spacer Fabric; Contact Geometry; Spherical Compression; Compression Strain